A MIXED-METHODS STUDY OF COMMUNITY-BASED HEALTH INTERVENTIONS AND UTILISATION OF CHILDHOOD HEALTHCARE SERVICES IN SOUTHERN SENATORIAL ZONE, PLATEAU STATE, NIGERIA - Otache, Emmanuel; Ameh, Nwamaka; Zingak, Deshi; Oniwinde, Nannyi (African Journal of Social and Behavioural Sciences, 2025)
Utilisation of childhood healthcare services remains low in many communities around the globe. This is particularly true for many low-income countries, including Nigeria, contributing to poor child health outcomes. This study explores the potential of community-based solutions to enhance access and service uptake in the Southern Senatorial Zone of Plateau State, Nigeria. A mixed-methods approach was adopted. Quantitative data were collected from 384 respondents using structured questionnaires, while qualitative insights were drawn from key informant interviews (KIIs) with healthcare workers, community leaders, women’s group leaders, and NGO representatives. The study was guided by Andersen’s Behavioural Model, the Social Ecological Model, Community Empowerment Theory, and the Diffusion of Innovations Theory. Findings show that 85.9% of respondents had neither contributed to nor benefited from community-based healthcare financing initiatives. Existing interventions, such as immunisation and nutrition education, face challenges including poor infrastructure, inadequate funding, and a shortage of trained personnel. Traditional and religious leaders play a crucial role in promoting healthcare awareness; however, persistent barriers, including poor road access, electricity shortages, insecurity, and household poverty, limit its utilisation. Community-driven strategies supported by local ownership and responsive health systems can improve childhood healthcare service uptake. Recommendations include strengthening community health insurance schemes, leveraging mobile health technologies, improving infrastructure, training and incentivising health workers, and fostering continuous community engagement. Achieving sustainable outcomes will require multi-sectoral collaboration, aligned policies, and context-specific implementation rooted in community realities.